2020
DOI: 10.7759/cureus.10951
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Mysteries of Restless Leg Syndrome

Abstract: Restless leg syndrome (RLS) or Willis-Ekbom disease (WED) is an under-diagnosed, chronic, and progressive primary sensory-motor disorder. It is characterized by an uncontrollable urge to move the legs due to uncomfortable and sometimes painful sensations, with a diurnal variation. RLS can lead to severe sleep disturbances, a usual cause of consultation. The pathophysiology is known partially, and it is believed that there is an association between the different variants of genetic mutations combined with dopam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…The exact mechanism for RLS in BID is not well understood; however, impaired striatal dopamine production is widely seen in animal models of ID displaying symptoms characterized as RLS. Tyrosine hydroxylase, the rate-limiting enzyme in dopamine production, requires iron as a cofactor, and its activity is shown to be impaired in animal models of RLS due to BID (96). Although iron administration is not recommended empirically, trials of oral ferrous sulfate with vitamin C can be considered for RLS patients with FTN levels ≤75 ng/mL (97).…”
Section: Restless Legs Syndromementioning
confidence: 99%
“…The exact mechanism for RLS in BID is not well understood; however, impaired striatal dopamine production is widely seen in animal models of ID displaying symptoms characterized as RLS. Tyrosine hydroxylase, the rate-limiting enzyme in dopamine production, requires iron as a cofactor, and its activity is shown to be impaired in animal models of RLS due to BID (96). Although iron administration is not recommended empirically, trials of oral ferrous sulfate with vitamin C can be considered for RLS patients with FTN levels ≤75 ng/mL (97).…”
Section: Restless Legs Syndromementioning
confidence: 99%
“…Our findings are consistent with research sourced from articles obtained from the PubMed database, which covered various aspects of RLS including gene variants, pathophysiology, and treatment methods, indicating that roughly 15% of the global population suffers from RLS. (Memon, 2020). Additionally, a study conducted on the correlation between RLS and sleep quality among the general population in Mangalore, India, revealed a prevalence of 11.9% among 202 participants, with 5 individuals already diagnosed with RLS.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary RLS may be in response to some existing neurological or nutrient-de cient disease or may be a symptom of a disease or disorder other than neurology. However, we also know that the secondary causes of RLS are associated with increased in ammation (15). Neuroimaging and humoral studies have shown that brain iron de ciency plays a role in the pathophysiology of RLS.…”
Section: Discussionmentioning
confidence: 99%